Models of Sentencing Children as Criminals (A Comparison of Several Countries) (Law Research Review Quarterly, 2022)
The sentencing of children in the context of children as perpetrators of crimes has its own complexities and challenges. On the one hand, law enforcement must be carried out in preventing and tackling crime, on the other hand the perpetrators of crimes are children who are legally regulated in judicial mechanisms and special systems. The model for punishing children in Indonesia has basically been regulated through the Juvenile Criminal Justice System and the Child Criminal Law. However, this model of punishment by several studies and related studies is said to be not perfect and adequate. This study aims to analyze and compare models of punishment for children as perpetrators of crimes in three countries: Indonesia, Thailand, and the Philippines. The method used in this research is a normative legal study. This method is used to analyze and compare several model practices of child punishment in three countries. This study uses a comparative law study approach and a statute approach. The location of this research is not carried out through field research but through library research and document studies. Supporting data in this study were also obtained from various data on the internet and printed sources.